Application of Blockchain Technology for iLearning Student Assessment - Sudaryono Sudaryono; Qurotul Aini; Ninda Lutfiani; Firman Hanafi; Untung Rahardja (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2020)
Blockchain is the core technology used to create cryptocurrencies, such as Bitcoin. As one part of the fourth industrial Revolution since the invention of steam engines, electricity, and information technology, blockchain technology has begun to be applied in areas such as finance, judiciary, and trade. Blockchain technology uses decentralized, distributed and transparency techniques for data security. This research aims to determine the implementation of blockchain technology in the field of education, especially in the Data Security section. The study uses two methods namely the mind mapping method and literature review. The results of this study showed that with the presence of blockchain technology, the data is more secure from attacks from both inside and outside because it passes through two levels of security, namely encryption and decentralized data.